EKONOMI KREATIF SEBAGAI IDE BISNIS SYARIAH: TINJAUAN LITERATUR TENTANG PERAN DAN PENGARUHNYA DALAM PEMBENTUKAN BISNIS KREATIF - Bayu Sudrajat; Salma Mutinida (LPPM Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
The creative economy has become an increasingly relevant topic in the context of modern business, while also growing awareness of sharia principles in the Muslim world. This article is a literature review which aims to investigate the role and influence of the creative economy in the formation of sharia creative businesses. Through data analysis from various literary sources such as scientific journals, books and articles, this study examines how the creative economy can support innovation, economic diversification and the promotion of Islamic culture in sharia creative businesses. The influence of the creative economy in sectors such as fashion, art, design and media is also analyzed in depth. The results provide insight into how the creative economy can play an important role in combining creativity, innovation and sharia principles to create ethical and competitive creative businesses in Indonesia. In this context, this literature research contributes to understanding the potential of the creative economy which can enrich sharia-based culture and economy in Indonesia.